Analysis of the Relationship between Field Work Practice and Self-Efficacy in Forming Career Decisions of Vocational High School Students - Miftahul Ulum; Siti Nur Aini; Erwan Widiyanto; Tuwoso Tuwoso (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the effect of Internship and self-efficacy in shaping student career decisions, partially or simultaneously. The method used in this research is a quantitative method with a correlational approach. The research was conducted on 150 students at SMK Kota and Pasuruan Regency in the competence of mechanical engineering expertise. Data collection techniques using a closed questionnaire. Data were analyzed using simple and multiple linear regression tests. The results showed that there is a significant positive relationship between Internship and career decision making with a correlation value (